PELATIHAN PERENCANAAN BISNIS BAGI KELOMPOK UMKM DI DESA KERTAYASA - Chintia Fitriani; Oktaviani Rita Puspasari; Yudi Febriansyah (Universitas Islam Al-Ihya Kuningan, 2025)
MSME actors in Kertayasa Village have not yet made business planning and budgeting, they still mix business funds with personal money. This has caused them difficulties in evaluating the profits earned and losses experienced. This activity aims to provide training and knowledge on how to plan business finances and create appropriate budgets. The implementation of this activity was carried out on October 6, 2023, and attended by 20 MSME actors. The main method used in this community service is the business planning training method for MSME groups and the delivery of material on how to create a business plan, followed by documenting the stages of business planning to then interpret the results of that business planning into the businesses they have or will undertake. The results of this activity enhance the understanding and skills of MSME actors in planning business finances and preparing budgets correctly, as evidenced by their ability to practice budget preparation, identify various costs, separate personal money from business funds, and project profits and losses in a simple way.